2020
DOI: 10.3389/fimmu.2020.00823
|View full text |Cite
|
Sign up to set email alerts
|

HIVconsv Vaccines and Romidepsin in Early-Treated HIV-1-Infected Individuals: Safety, Immunogenicity and Effect on the Viral Reservoir (Study BCN02)

Abstract: Kick&kill strategies combining drugs aiming to reactivate the viral reservoir with therapeutic vaccines to induce effective cytotoxic immune responses hold potential to achieve a functional cure for HIV-1 infection. Here, we report on an open-label, single-arm, phase I clinical trial, enrolling 15 early-treated HIV-1-infected individuals, testing the combination of the histone deacetylase inhibitor romidepsin as a latency-reversing agent and the MVA.HIVconsv vaccine. Romidepsin treatment resulted in increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 58 publications
1
83
2
Order By: Relevance
“…This was not the case following HIVconsv vaccination, which induced prominent Pol epitope responses directly proportional to the relative length of the Pol segment in the HIVconsv sequence (Table 3). These results would support the ability of a potent vector delivery to (re)focus immune responses including CD4 + T cells toward regions that are generally subdominant in natural HIV-1 infection [59,60]. A different study reported over half of tested variant peptides not being recognized by CD4 + T cells [51], emphasizing even for the more promiscuous HLA class II molecules peptide selectivity and the importance of focusing on and matching vaccine responses to less variable regions of the HIV-1 proteome.…”
Section: Discussionmentioning
confidence: 71%
“…This was not the case following HIVconsv vaccination, which induced prominent Pol epitope responses directly proportional to the relative length of the Pol segment in the HIVconsv sequence (Table 3). These results would support the ability of a potent vector delivery to (re)focus immune responses including CD4 + T cells toward regions that are generally subdominant in natural HIV-1 infection [59,60]. A different study reported over half of tested variant peptides not being recognized by CD4 + T cells [51], emphasizing even for the more promiscuous HLA class II molecules peptide selectivity and the importance of focusing on and matching vaccine responses to less variable regions of the HIV-1 proteome.…”
Section: Discussionmentioning
confidence: 71%
“…The GRIN immunogen was a fusion of full-length Gag, Reverse Transcriptase (RT), Integrase and Nef, and was delivered by replication-deficient human adenovirus serotype 35 (Ad35-GRIN or A) [ 66 , 67 ]. Ad35-GRIN substituted for the simian adenovirus serotype 63-vectored HIVconsv vaccine used in previous trials [ 50 , 56 , 57 , 58 , 59 ], to which we lost freedom to operate following GlaxoSmithKline acquisition of the ChAdV63 vaccine vector. GRIN had an extensive sequence match to HIVconsv as GRIN covered almost 80% of all HIVconsv ( Figure 1 ) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, our working hypothesis postulates that focusing vaccine-elicited T cells on the functionally conserved regions of HIV-1, which are common to most global variants and are hard to mutate, will be effective in slowing and controlling HIV-1 infection [ 41 , 42 , 43 , 50 , 51 , 52 , 53 , 54 , 55 ]. These regions contain epitopes typically subdominant in natural HIV-1 infection, but are capable of inducting robust T-cell responses when delivered by a potent vaccination regimen [ 50 , 56 , 57 , 58 , 59 , 60 ]. Such vaccine-elicited responses thus represent a rich source of previously undescribed, potentially important epitopes [ 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total DNA is the quantification of all forms of HIV-DNA, integrated and unintegrated, coding for both competent and defective viruses reflecting the global size of the reservoir giving an overview of its distribution in the body at all stages of the disease [ 66 ]. Several studies testing different therapeutic based-vaccine strategies (alone, boosted or combined) [ 33 , 37 , 44 , 45 , 50 , 65 , 67 ] ( Table 4 ), have measured total DNA as a reservoir biomarker and found different results when assessing the effect on pVL during ATI. Some of these studies, one conducted in patients that started ART during acute infection [ 45 ], have described a correlation between a smaller size of baseline CA-DNA and longer time to resume ART after ATI [ 33 , 50 ], but some others found no relation [ 37 , 44 , 67 ].…”
Section: Surrogate Markers Of Viral Response During Atimentioning
confidence: 99%
“…Several studies testing different therapeutic based-vaccine strategies (alone, boosted or combined) [ 33 , 37 , 44 , 45 , 50 , 65 , 67 ] ( Table 4 ), have measured total DNA as a reservoir biomarker and found different results when assessing the effect on pVL during ATI. Some of these studies, one conducted in patients that started ART during acute infection [ 45 ], have described a correlation between a smaller size of baseline CA-DNA and longer time to resume ART after ATI [ 33 , 50 ], but some others found no relation [ 37 , 44 , 67 ]. Neither of these studies found any significant effect on CA-DNA of any of the studied products, although a study evaluating a DC-based vaccine found that the magnitude of T cell responses measured by IFNγ ELISPOT during the vaccination period was an independent predictor of total DNA during ATI and also found a correlation between total DNA levels and pVL set point during ATI [ 44 ].…”
Section: Surrogate Markers Of Viral Response During Atimentioning
confidence: 99%